Low‐status aversion: the effect of self‐threat on willingness to buy and sell. Issue 11 (8th May 2014) - Pan, Caitlin; Pettit, Nathan C.; Sivanathan, Niro; Blader, Steven L.
Abstract Consumption decisions are inherently rooted in both what to consume and what to forgo. Although prior research has focused on consumption, we instead examine what compels consumers to steer clear of particular goods. In two studies, we demonstrated that individuals experiencing self‐threat avoid low‐status goods to prevent further damage to their self‐worth. Individuals facing self‐threat showed a decreased willingness to buy (Study 1), and a correspondingly greater willingness to sell (Study 2) low‐status goods, as compared with nonthreatened individuals. Notably, these effects emerged even when such behaviors were associated with economic costs (Study 2). Together, these results highlight how the motive to preserve the self can affect market exchanges, thereby painting a more complete portrait of the relationship between consumption, status, and the self.